Assessing the Impact of Workplace Harassment on Turnover Intention: Evidence from the Banking Industry - José Moleiro Martins; Muhammad Farrukh Shahzad; Iqra Javed (Ital Publication, 2023)
Workplace harassment is considered one of the main issues in the banking sector, which is subject to major human and labor rights violations. In the current global situation, harassed employees are prone to high turnover and become less productive due to undue stress and unstable mental health. Thus, this study aims to measure the influence of workplace harassment on the turnover intentions of employees in Pakistan's banking industry. This study assessed how workplace harassment affects employees' silence, mental stress, turnover intention, and the moderating role of psychological contract breaches. The study advises significant measures to prevent assault by retaining and empowering workers to work effectively. The data were collected through an adopted questionnaire from 416 respondents from the banking sector in Lahore, Pakistan. Variance-based structural equation modeling (PLS-SEM) was used. The results reveal that workplace harassment significantly and positively impacts turnover intention. Additionally, employee silence and mental stress have significantly mediated the relationship between workplace harassment and turnover intention. However, psychological contract breaches have significantly moderated the relationship between employee silence and workplace harassment. This study aims to promote equal employment opportunities where they can raise their voices about misconduct and lower the employee turnover ratio. Doi: 10.28991/ESJ-2023-07-05-016 Full Text: PDF